Risks of the insurance company: classification and methods of analysis - Дорошенко, Н. О.; Загорська, Д. М.; Суй, І (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2018)
The purpose of the article was to develop a risk classification of the insurance company, identify the shortcomings and advantages of existing methods of risk analysis and measures to reduce the risks of insurance companies. Group presented risk assessment methods is, according to the author, rather conditional, because risk identification can be carried out using techniques and technologies analysis and evaluation of all types of risks, and vice versa. An analysis of the studies of Ukrainian and foreign authors showed that there are a large number of classification features and types of risks and the absence of a single universally accepted classification of risks, which in our opinion, the author is associated with the unsystematic conceptual apparatus of the theory of risks and a wide variety of their manifestations in the practical activities of enterprises. Therefore, the definition of "risk" is clarified and it is emphasized that the modern concept of management of operating activities in an insurance company relies on the methodology of its operating business processes: the conclusion and maintenance of insurance contracts, underwriting, reinsurance and settlement of losses. The classification of risks of the insurance company and the logical connections of groups of general and specific risks is proposed, combining them into 4 types: risk of accidental risk (accidental and dangerous events), financial risk, operational risk - probability of occurrence of losses due to incorrect work of personnel, internal systems or under the influence of external factors and strategic risk. Considered is the estimation of the efficiency of the insurance company with the use of EVA and RAROC indicators, which allow to assess the financial position of the company and its effective management, or its subdivision. Considered is the application of stress testing and individual measures to reduce financial risk for effective insurance of risks of an insurance company.